Optimalisasi Supervisi Kepala Ruangan terhadap Pelaksanaan Handover - Marbun, Yusniaty; Afriani, Tuti; Nasri, Khairul; Herawani, Herawani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to design a proposal for improving the supervision of the head of the room in the implementation of handover in the inpatient room of South Jakarta General Hospital. The research method used is a case report. The study's results showed that there was already a 40% improvement, for example, the afternoon handover from 14.00 to 13.45 had started and the morning shift began at 08.00, 40% 07.45 / 07.30. For the completeness of handover nurses between the previous shift and the next shift from 5 rooms, 60% had improved, whereas, before the socialization, it was only 40%. For the completeness of the number of nurses who participated in the handover, The head of the room participated in visiting patients with the team, for the morning shift 80% was realized, and for the afternoon shift 40% was realized. Patients were led to pray, 40% realized. In conclusion, optimization of the head of the room's supervision of the implementation of the handover has a positive impact on improving the quality of health services in the inpatient room of South Jakarta General Hospital. Keywords: Handover, Head of Room, Supervision